Rates and predictors of breach, revocation and hospital readmission of conditionally released Forensic Patients in New South Wales, Australia - Lyons, Georgia (The journal of forensic psychiatry & psychology, 2022)
Forensic patients who have been referred for secure hospital care after serious offences committed whilst mentally ill often have complex mental health conditions and risks that must be carefully considered in planning their safe release into the community. This study aimed to establish the rates and predictors of several post-release outcomes in a cohort of conditionally released forensic patients in NSW, including breaches of conditions, revocation of conditional release and readmission to hospital. Among the 245 patients who were conditionally released during the study period, just over half (57.1%; n = 140) had at least one recorded breach, revocation or readmission. Independent predictors of those outcomes included not being engaged in employment or study at the time of the index offence, having a comorbid diagnosis of substance use disorder, history of head injury and having a non-homicide-related index offence. These findings have implications for post-release planning and interventions provided by forensic mental health services.